“ESPAÇO ESCOLAR, HOMOSSEXUALIDADES E PRÁTICA DISCURSIVA DOCENTE EM PONTA GROSSA, PARANÁ” - Santos, Adelaine Ellis Carbonar dos (2015)
This research shows how the discourse of teachers in relation to homosexualities composes the school environment in Ponta Grossa, Paraná. To give intelligibility to the chosen phenomenon, there were 17 interviews with 17 teachers who work /worked in public high schools of that city. The interviews show that homophobia is an element that constitutes the school environment through power relations that are embedded in the teachers speeches. Also, we conclude not only the school environment as a interdicted space for homossexuals, but also the higher education institutions, as high school drop out contributes to the non-completion of basic education. Still, the initial teacher education is marked by the absence of discussions regarding the issue so that affect the approach to sexuality in school, although a portion of teachers affirms the importance of this issue when considering the recognition of homosexualities as an important aspect in the social and educational development. This recognition given to the theme enables teaching practice aimed at destabilizing heteronormative standards at the time they understand the homosexualities as a valid form of sexual expression as much as heterosexuality, giving to the school environment one of the possibilities of subversion of the standard.